Corrigendum to “Nitrogen losses trade-offs through layered fertilization to improve nitrogen nutrition status and net economic benefit in wheat-maize rotation system” [Field Crops Res. 312 (2024) 109406] - Changhong Liu; Shengyan Pang; Xiufeng Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Dong Wang (Field Crops Research, 2026)

Moderate deep banding of phosphorus enhanced winter wheat yield and fertilizer uptake efficiency by promoting nutrient absorption and translocation of pre-anthesis nutrient - Yang Zhou; Zhenyan Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Shubo Gu; Jing Yang; Dong Wang (Field Crops Research, 2025)

The Neurocomputational Mechanism Underlying Decision-Making on Unfairness to Self and Others - Lanxin Luo; Han Xu; Xia Tian; Yue Zhao; Ruoling Xiong; Huafeng Dong; Xiaoqing Li; Yuhe Wang; Yue‑Jia Luo; Chunliang Feng (Neuroscience Bulletin, 2024)

Nitrogen losses trade-offs through layered fertilization to improve nitrogen nutrition status and net economic benefit in wheat-maize rotation system - Changhong Liu; Shengyan Pang; Xiufeng Li; Yongqiang Li; Jinwei Li; Ruoling Ma; Xiang Lin; Dong Wang (Field Crops Research, 2024)

Effects of Lateral Flows on the Supercavitation and Hydrodynamic Characteristics of Underwater Series and Parallel High-Speed Projectiles - Lite Zhang; Chengwei Zhang; Huixia Jia; Ruoling Dong (Journal of Marine Science and Engineering, 2023)
In this paper, the supercavitation of the parallel and tandem projectiles moving underwater with high-speed under the condition with/without lateral flows is numerically simulated by the volume of fraction (VOF) model. The motion of the projectiles was handled by the overlapping grid and six degrees of freedom (DOF) techniques. The supercavitation evolution and the hydrodynamic characteristics of the projectiles were analyzed for the parallel and tandem projectiles under different conditions. The results show that the cavity shape is symmetrical under the condition without lateral flows, but is no longer symmetrical under the conditions with lateral flows. The asymmetry of the cavity contour increases with the velocity of the lateral flow. For the parallel projectiles, the change trends of the axial velocity of projectile 1 and projectile 2 are nearly the same. The offset velocity of projectile 1 and projectile 2 increases with the increase in the velocity of the lateral flow. The deflection angle of projectile 1 decreases with the increase in the lateral flow velocity but that of projectile 2 increases with the increase in the lateral flow velocity. At t = 3.0 ms, the deflection angle of projectile 2 is up to 20° under the condition of the lateral flow velocity of 11.25%, while the deflection angle of projectile 1 and 2 under other conditions is in the range of 5°. For the tandem projectiles, the axial velocity of projectile 1 gradually decreases. The change trend of the axial velocity of projectile 2 at first is the same as that of projectile 1, and then the change is dependent on the velocity of the lateral flow. Under the condition of the lateral flow velocity with 11.25%Vp, projectile 2 cannot enter the cavity of the front projectile. The change trend of the axial velocity of projectile 2 is similar as but somewhat slower than that of projectile 1. For the parallel projectiles, the ballistic stability of the projectile on the oncoming side is better than that of the projectile on the backflow side. Whether parallel or tandem projectiles, the ballistic stability of projectile 2 becomes worse with the increase in the lateral flow velocity.

Residential greenness attenuated associations of long-term exposure to air pollution with biomarkers of advanced fibrosis - Jian Hou; Xiaotian Liu; Tantan Zuo; Runqi Tu; Xiaokang Dong; Ruiying Li; Mingming Pan; Ruoling Chen; Shanshan Yin; Kai Hu; Zhenxing Mao; Wenqian Huo; et al. (Environmental Science and Pollution Research, 2022)